The Impact of Physics Co-curricular Activities Based on Makassar Local Wisdom on Improving the Pancasila Student Profile and Learning Satisfaction - Martawijaya, M. A.; Sujiono, Eko Hadi; Halim, Anis Diyana; Siew Wei, Tho; Mahir, Mahir; Palloan, Pariabti; Zharvan, Vicran (Jurnal Pendidikan IPA Indonesia, 2025)
Pancasila education shapes students’ character and national identity. Integrating local wisdom in co-curricular activities strengthens Pancasila values in modern learning. Despite the flexibility of co-curricular activities in reinforcing physics concepts and the Pancasila Student Profile (P3), educators rarely utilize or neglect them entirely. This study aims to improve P3 and learning satisfaction through physics co-curricular activities based on Makassarese local wisdom. This study used a mixed-methods sequential explanatory design. The quantitative method used a pre-experimental design with a one-group pretest-posttest type to measure changes in P3, and the qualitative method used an open questionnaire to measure students’ learning satisfaction. This activity integrates the 21st-century learning approach with the practice of a’bulo sibatang through physics measurements by 31 high school students. The study showed a significant improvement in students’ P3 (p < 0.05), with an N-Gain of 48.39% in the low category and 51.61% in the medium category. All students expressed positive learning satisfaction towards the Makassarese local wisdom-based physics co-curricular activities, although some experienced difficulties in certain aspects. This study concludes that co-curricular physics activities based on Makassarese local wisdom effectively improve students’ P3 and positive learning satisfaction. In addition, this study also has an impact on preventing the erosion of Makassarese cultural identity and improving students’ academic understanding.